2015
DOI: 10.1590/0104-1169.0377.2575
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of indicators and respective definitions for the nursing outcome Swallowing Status

Abstract: OBJECTIVE: to develop indicators for the nursing outcome Swallowing Status and the respective conceptual and operational definitions validated by experts and in a clinical setting among patients after having experienced a stroke. METHOD: methodological study with concept analysis and content and clinical validations. The Content Validation Index was verified for the scores assigned by 11 experts to indicators. Two pairs of nurses assessed 81 patients during the clinical validation: one pair used an instrument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 17 publications
1
20
0
5
Order By: Relevance
“…In this study, results confirmed the unidimensionality of Swallowing status outcome. Previous methodological study with concept analysis and content and clinical validations contributed to refine this outcome (Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this study, results confirmed the unidimensionality of Swallowing status outcome. Previous methodological study with concept analysis and content and clinical validations contributed to refine this outcome (Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…A nurse provided a score using a value ranging from 1 (worst result) to 5 (best health status). Operational definitions were previously developed for each indicator to allow a more accurate result analysis performed by the nurse (Oliveira et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NOC presents advantages such as reduced documentation time, better patient satisfaction and results, greater uniformity in the evaluation of the professional nurse and improved quality of care ( 9 - 10 ) . This study is justified by the importance of developing a clinical evaluation focused on the condition of eye health and prevention of adverse events to the patient, using a taxonomy composed of a set of indicators to direct the care and determine interventions that provide positive results.…”
Section: Introductionmentioning
confidence: 99%